Setting and prioritizing evidence-informed policies to control childhood obesity in Iran: a mixed Delphi and policy dialogue approach - Fatemeh Toorang; Amirhossein Takian; Hamed Pouraram; Parisa Amiri; Zahra Abdullahi (BMC Pediatrics, 2022)
Highlights Childhood obesity is a gateway to several diseases in the near and distant future. The prevalence of childhood obesity is high and is increasing alarmingly in Iran. Several policy options are proposed by scientists and other stakeholders to combat childhood obesity in Iran. Stakeholders believed that healthy schools, creating healthy environments in kindergartens and other child care centers, subsidizing healthy foods, educating healthy lifestyles in mass media, and increasing access to physical activity facilities with priority given to deprived areas are the most effective and feasible policies in controlling childhood obesity.